Need of Small Group Teaching and Hybrid Models in Medical Colleges to Combine Problem Based Learning (PBL) and Traditional Methods in Curriculum - Haque, Anwar Ul (International Journal of Pathology, 2021)
During the last five decades, new understanding has emerged from cognitive science research about the nature of learning. There has been more emphasis on teaching in small groups instead of traditional large group lectures. The introduction of problem based learning (PBL) is a paradigm shift in pedagogy from teaching to active learning7. There are few medical institutions in Pakistan which have incorporated PBL in the curriculum. The traditional teaching is still the main teaching methodology in large majority of medical colleges in Pakistan. It may not be possible for all medical institutions to adopt PBL curriculum as it needs allocation of space, huge financial and human resources for its implementation. At the same time keeping the traditional methods as the main teaching strategy will not satisfy and meet the needs of medical students. It is only about 5% which can be retained from what is taught even in the most charismatic and inspirational lecture. In prevailing circumstances there is need of hybrid curricula to combine the PBL and traditional methods. It is especially useful for those colleges that want to benefit from the advantages of PBL methodology but do not want a complete reform to switch to an entirely PBL-based curriculum.